Technological Overview: Analysis of Patents Related to the Use of Core-Shell Catalysts and ALD in Solid Oxide Fuel Cells - Iuri Dantas Passos da Mota; Marcos Makoto Toyama; Gerhard Ett; Lilian Lefol Nani Guarieiro (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
This study analyzes patents registered between 2010 and 2025 involving solid oxide fuel cells (SOFC), atomic layer deposition (ALD), and core-shell structures. Data from Lens.org show that the combination of ALD and core-shell accounts for the largest number of registrations, reflecting broad industrial applicability. Combinations with SOFCs, on the other hand, have a low incidence, suggesting an area in the early stages of intellectual property protection. Only two registrations simultaneously associate SOFC, ALD, and core-shell, evidencing a little-explored technological frontier. Most filings occur in the US, Japan, South Korea, and the European Patent Office (EPO), with an emphasis on companies and research institutions. Brazil's presence is limited to one registration involving SOFC and core-shell, indicating the need for greater investment in applied research and intellectual property protection. The interface between these technologies represents an emerging niche with high innovative potential.